2009
DOI: 10.1016/j.ultsonch.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Physical insights into the sonochemical degradation of recalcitrant organic pollutants with cavitation bubble dynamics

Abstract: This paper tries to discern the mechanistic features of sonochemical degradation of recalcitrant organic pollutants using five model compounds, viz. phenol (Ph), chlorobenzene (CB), nitrobenzene (NB), p-nitrophenol (PNP) and 2,4-dichlorophenol (2,4-DCP). The sonochemical degradation of the pollutant can occur in three distinct pathways: hydroxylation by ()OH radicals produced from cavitation bubbles (either in the bubble-bulk interfacial region or in the bulk liquid medium), thermal decomposition in cavitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 45 publications
4
49
0
Order By: Relevance
“…The results of this work confirm this aspect and agree well with similar observations in the literature [21,22]. However, it should be noted that no such systematic studies have been reported in the literature on the degradation of different solvents using hydrodynamic cavitation though some single component studies were reported using conventional cavitating devices such as an orifice.…”
Section: Effect Of Nature Of Solventsupporting
confidence: 92%
“…The results of this work confirm this aspect and agree well with similar observations in the literature [21,22]. However, it should be noted that no such systematic studies have been reported in the literature on the degradation of different solvents using hydrodynamic cavitation though some single component studies were reported using conventional cavitating devices such as an orifice.…”
Section: Effect Of Nature Of Solventsupporting
confidence: 92%
“…Since the C p /C v ratio of N 2 (g) is high (1.543) the bubble diameter increase during cavitation process resulting in high OH· ions (Mendez-Arriaga et al 2008;Psillakis et al 2003). In this study, it was found that N 2 (g) increase the OH· ions through sonication of less hydrophobic PAHs (data not shown) by increasing the temperature and bubble diameter as reported by Sivasankar and Moholkar (2009).…”
Section: Effect Of Aeration On the Removal Of Pah At Increasing Sonicsupporting
confidence: 55%
“…We attribute this result to the presence of oxygen in air bubble that conserves the radicals formed out of dissociation of water vapor. 27,28 3. With rise in static pressure to 200 kPa (or 2 bar), both chemical and physical effects of cavitation bubbles get eliminated.…”
Section: Simulations Resultsmentioning
confidence: 99%
“…27,28 The dissolved oxygen can help conservation of the • OH radicals generated through Fenton reactions as well as cavitation bubbles through following reaction…”
Section: Contemplations and Conjecturesmentioning
confidence: 99%